Economic evaluations in medical technological innovations a mapping review of methodologies - C. van Lieshout; G. W. J. Frederix; L. Schoonhoven (Cost Effectiveness and Resource Allocation, 2024)
Abstract Rationale Economic evaluations play an important role in the development and implementation of healthcare innovations. For pharmaceutical products, the methodologies used are laid down in guidelines, whereas for medical technologies the guidelines are not as strenuous. The aim of this review was therefore to analyze what types of methodologies are used in economic evaluations of medical technologies. Methods We performed a mapping review to identify economic evaluations for medical technologies. We decided to limit our search to one year (2022) and included cost utility and cost effectiveness analyses in which health technologies were evaluated. For each included study we identified the main methodological characteristics. Results A total of 364 papers were included in the analysis, 268 (74%) contained cost-utility analyses and 91 (25%) cost-effectiveness analyses. A model was used in 236 (64%) analyses, 117 analyses were trial based evaluations. Probabilistic sensitivity analyses and/or bootstrapping was performed in 266 (73%) analyses. Deterministic sensitivity analyses were used in 306 (84%). Time horizon and perspective were underreported in 15–25% of the included studies. Conclusions This review shows the wide range of methodologies used in economic evaluations as well as the extent and rigor in which these methodologies are used. Many of the included papers did no use or did not sufficiently report the use of appropriate standard methods. This may lead to research waste, a delay in successful implementation of valuable innovations and in the end may delay improvement patient outcomes.